Rancang Bangun 3D Printer FDM Model Cartesian Berbasis Arduino - Mardiyana, Dani; Sulaiman, Zaid; Ihsan, Saepul; Ridha, Fabrobi; Rahman, Taufik (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
Prototyping using the manual method consumes a lot of time, raw materials, and is often inaccurate. The 3D printer is a more quick and detailed method in the manufacture. Research on 3D printers by previous researchers still lacks product dimensional accuracy, and stringing still occurs. This research on the design of the Arduino-based Cartesian FDM 3D printer was carried out to produce a 3D printer frame that is sturdy, has good accuracy, and overcomes stringing. The methodology on the design is where the 3D printer machine is designed and built, then its performance is tested. The 3D printer design has dimensions of 434 x 470 x 610 mm with a work area of 220 x 220 x 233 mm. The frame is simulated with FEA with a safety factor of 15 ul. The 3D printer control uses Arduino Mega 2560 for operation. The results of the 3D printer performance test have succeeded in eliminating stringing with an X-axis product accuracy of 99.48%, Y-axis 99.24%, and Z-axis 98.46%.